Implementation of Healthy Living Behavior of Early Childhood during the Covid-19 Pandemic - Dian Putri Pangestu; Na’imah Na’imah; Raden Rachmy Diana; Khamim Zarkasih Putro; Dandia Ayu Saraswati (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
Maintaining health is very important to be applied from an early age, especially during the covid-19 pandemic. This is important because children are prone to disease because their immune system is not as strong as adults in general. This study aims to present and describe the implementation of healthy living behaviors of early childhood during the covid-19 pandemic. This research includes a type of field research with a qualitative approach. The data source uses primary data in interviews, observations, documentation, and questionnaires—data analysis techniques using the Miles and Huberman models. The results of this study show that the implementation of healthy living behaviors of early childhood has been carried out well following the proposal of the Directorate of Paud Development in 2020 on four healthy living behaviors in schools, namely: washing hands with soap, drinking water, and eating healthy and hygienic food, as well as disposing of waste in its place and keeping the environment clean and safe.